Impacts of Shifting Responsibility for High-Cost Individuals on Health Insurance Exchange Plan Premiums and Cost-Sharing Provisions - Sankar Mukhopadhyay; Jeanne Wendel; Miaomiao Zou (Institute of Labor Economics (IZA), 2018)
States with Section 1332 Waivers to operate high-risk pools (HRPs) or reinsurance programs can receive federal pass through funds equal to reductions in federal expenditures generated by the Waiver. Shifting financial responsibility for high-cost individuals out of the Health Insurance Exchange (HIX) markets is expected to reduce federal expenditures for Advanced Premium Tax Credits, by reducing HIX plan premiums. Simulation models predict that a new HRP or reinsurance program would trigger premium reductions ranging from 7% to 23%. These models assume that insurers do not adjust plan cost-sharing requirements or plan generosity. However, federal requirements specifying the Medical Loss Ratio and plan Actuarial Values give insurers incentives to make multidimensional adjustments. We use plan level fixed effects to generate difference-in-difference estimates of insurer responses to closures of state-operated HRPs during 2014-2016. Silver plan premiums increased 7.7%, deductibles increased 41%, and Maximum-Out-Of-Pocket (MOOPs) expenditures increased 24% following closure of a state HRP.
Keywords: I11; I13; I18; 330; high risk pools; insurance premium; health insurance exchanges; cost-sharing